2013
DOI: 10.1038/jid.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Factors Are Associated with Childhood Eczema Prevalence in the United States

Abstract: Atopic dermatitis (AD, atopic eczema) is driven by a complex relationship between genetic predisposition and environmental exposures. We sought to determine the impact of specific climatic factors on the US prevalence of AD. We used a merged analysis of the 2007 National Survey of Children's Health from a representative sample of 91,642 children age 0–17 years and the 2006–2007 National Climate Data Center and Weather Service measurements of relative humidity (%), indoor heating degree days (HDD), clear sky UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
180
4
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 247 publications
(207 citation statements)
references
References 26 publications
10
180
4
12
Order By: Relevance
“…26 Indeed, previous reports have shown that AD symptoms correlate positively with latitude and negatively with annular outdoor temperature. 27 These data may also suggest that females are susceptible to environmental factors with respect to AD. Our data also revealed a significant geographic variability in disease prevalence in Korea with a higher prevalence in lower latitude cities and province.…”
Section: Discussionmentioning
confidence: 92%
“…26 Indeed, previous reports have shown that AD symptoms correlate positively with latitude and negatively with annular outdoor temperature. 27 These data may also suggest that females are susceptible to environmental factors with respect to AD. Our data also revealed a significant geographic variability in disease prevalence in Korea with a higher prevalence in lower latitude cities and province.…”
Section: Discussionmentioning
confidence: 92%
“…Indoor relative humidity is inversely associated with eczema prevalence, i.e. higher indoor humidity is associated with lower rates of AD [84,90]. However, conflicting results have been found about whether outdoor humidity is positively or inversely associated with AD prevalence [85,87,88,90].…”
Section: 42mentioning
confidence: 84%
“…higher indoor humidity is associated with lower rates of AD [84,90]. However, conflicting results have been found about whether outdoor humidity is positively or inversely associated with AD prevalence [85,87,88,90]. Further epidemiological research on humidity and AD is warranted, particularly because humidifiers are commonly used as an adjunctive treatment by AD patients.…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations